A gain of function p53 gene mutant promotes growth suppression in human liver cancer cells - Nor Adzimah Johdi,; Siti Nurmi Nasir,; A. Rahman A. Jamal, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Primary liver cancer is one of the most common cancer in the world with highest cancer mortality rate. The most common type of primary liver cancer is hepatocellular carcinoma (HCC). There are many risk factors for liver cancer and currently available treatments for HCC are largely inadequate. Gene mutation and dysfunction of p53 are common and is recognized as an important molecular event in hepatocarcinogenesis. Therefore, replacement of the aberrant p53 gene is an attractive approach in the treatment of HCC providing an alternative treatment for primary HCC. In this study, we assessed whether the transfection with wild-type p53 gene is able to restore the pro-apoptotic effects and evaluate the feasibility of gene therapy in fixing a faulty p53 molecule. We established a non-viral cationic lipid-based p53 gene delivery into two human HCC cell lines namely HLF and PLC/PRF/5 cells. Both cell lines have mutations in the p53 gene. We compared the results with the normal liver cell line, WRL68, that constitutively expresses the wild-type p53 gene. In this study, the introduction of wild-type p53 gene into HLF and PLC/PRF/5 cells resulted in an increased of p53 gene expression, protein expression and cells growth inhibition shown in MTS reduction cell viability assay, FITC-Annexin V and PI apoptosis assay, western blot and caspase activity assay. In summary, the study provides a promising therapeutic approach for p53 gene delivery into HCC patients. The p53 gene delivery can be instituted together with chemotherapy as a combination treatment to induce apoptosis.